Results of Controlled Burning in the Sal Plantations of Bengal - Rawat, A. S. (Indian Forester, 1949)
(1) Change in the undergrowth. After the first few years of burning, there were clear indications of the evergreen undergrowth, such as ferns and Piper spp., getting reduced, and it was expected that the annual burning would eventually eradicate these species, especially Pollinia ciliata (sau grass) which prevents the establishment of sal, and that Imperata arundinacea (thatch) would replace Pollinia; but the incidence of the thatch is small and it is replacing the sau grass in openings only. After about 15years of annual burning, most of the evergreen species still persisted. Burning did not lessen the number of climbers, nor did it kill them. They remained more or less the same in the burnt and unburnt plots, though slightly less luxuriant in the former. (2) Cost if Climber cutting. Only in the case of Buxa division was the cost of climber cutting significantly less for the burnt plots compared to the unburnt ones. This significant reduction in the cost may be due, to the mechanical advantage of the cleaner ground in the burnt plots which makes it easier to the labour to work in them. (-3) Rate of growth and volume increment of sal. Controlled burning did not produce any beneficial effect on the diameter and height increment of sal; in some cases it has rather produced, with regard to diameter, the reverse effect. On this evidence we may therefore state that burning is setting back the diameter development if sal plantations in Bengal to some extent. It makes the soil drier which perhaps leads to reduction in the rate of sal growth but height growth has remained unaffected. The present technique of clearfelling the climax forest, burning the debris and planting sal are perhaps responsible for the establishment and good growth of sal in the moist soils of the Bengal plantations.